Initial Reports of the Deep Sea Drilling Project 1986
DOI: 10.2973/dsdp.proc.90.138.1986
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Stratigraphy and Structure Adjacent to an Evolving Plate Boundary, Western Chatham Rise, New Zealand

Abstract: Seismic profiles obtained from the eastern side of New Zealand, in transit to and from Site 594, illustrate the evolution of the western end of the Chatham Rise and the southern extremity of the Hikurangi Trough. They show several unconformities and several major changes in tectonic and depositional regime. The unconformities represent major changes in oceanic circulation, possibly triggered by large lowerings of sea level in the late Oligocene and late Miocene. Tectonism is exemplified by a Late Cretaceous ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…A similar increase in terrigenous sedimentation associated with changes in seismic impedance or sequence architecture have been recorded on the southern flank of the Chatham Rise at DSDP site 594 (Lewis et al 1986;Nelson 1986) and on the South Island continental margin in the late Miocene (Wood et al 1989). The late Miocene (c. 9-10 Ma) age of reflector LM coincides with the onset of significant tectonic shortening within the New Zealand plate-boundary zone and regional uplift (Walcott 1978).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…A similar increase in terrigenous sedimentation associated with changes in seismic impedance or sequence architecture have been recorded on the southern flank of the Chatham Rise at DSDP site 594 (Lewis et al 1986;Nelson 1986) and on the South Island continental margin in the late Miocene (Wood et al 1989). The late Miocene (c. 9-10 Ma) age of reflector LM coincides with the onset of significant tectonic shortening within the New Zealand plate-boundary zone and regional uplift (Walcott 1978).…”
Section: Discussionsupporting
confidence: 56%
“…2). A packet of strong, parallel reflectors below this lower wedge has been traced in airgun profiles to the Canterbury shelf, where it represents the Oligocene Amuri Limestone (Lewis et al 1986;Wood et al 1989).…”
Section: Deep-sea Pliocene-pleistocene Sequences: Products Of Alternamentioning
confidence: 98%
See 1 more Smart Citation
“…Gibson, 1971;Mobil, 1972;Australian Gulf, 1973;Houtz and Aitkin, 1973;Hayes et at., 1976;Lewis et at., 1985) and numerous oceanographic surveys.…”
Section: Geological Settingmentioning
confidence: 99%
“…In 1985 Glomar Challenger drilled a hole, DSDP 594, about 80 km to the south. Lewis et al, (1985) described some of the seismic stratigraphy in the region of knolls in the light of the drillhole stratigraphy and of regional seismic stratigraphic syntheses by the New Zealand Geological Survey (Wood et al, in press). Lewis et al, concluded, from the interpreted age of infilling of scour moats around some of the knolls, that they date from the Miocene.…”
Section: Introductionmentioning
confidence: 99%